The Black radical imagination: a space of hope and possible futures - Hill-Jarrett, Tanisha G. (Frontiers in Neurology, 2023)
The radical imagination entails stepping outside the confines of the now and into the expansiveness of what could be. It has been described as the ability to dream of possible futures and bring these possibilities back to the present to drive social transformation. This perspective paper seeks to provide an overview of the radical imagination and its intersections with Afrofuturism, a framework and artistic epistemology that expresses the Black cultural experience through a space of hope where Blackness is integral. In this paper, I propose three processes that comprise the radical imagination: (1) imagining alternative Black futures, (2) radical hope, and (3) collective courage. I consider the neural networks that underlie each process and consider how the Black radical imagination is a portal through which aging Black adults experience hope and envision futures that drive social change. I conclude with considerations of what brain health and healing justice looks like for aging Black Americans— specifically, how invocation of the Black radical imagination may have positive brain health effects for a demographic group at increased risk for Alzheimer’s disease and related dementias.